Simulação computacional fluidodinâmica e termoquímica de reator em leito fluidizado destinado a gaseificação de combustível derivado de resíduos sólidos urbanos - Monteiro, Vitor Alberto Lemes (2024)
Faced with the issue of sustainability regarding the disposal of urban waste, produced worldwide at a rapid pace, several approaches and technologies are presented aimed at energy recovery from discarded waste, the so-called Waste-to-Energy technologies. In this context, technologies involving fluidized bed gasification assume great prominence in cademic work and laboratory developments. However, its large-scale physical experimentation, especially involving waste that can produce gases and other harmful effects on health and the environment, is restricted, costly and high risk. The present work aimed to develop a computational model capable of reproducing the physical experimentation of a real large-scale gasification reactor. The developed CFD model proved capable of coherently replicating the results obtained in physical experiments, allowing valuable inferences about the fluid dynamic flow with detailed, cost-effective analysis of the equipment's behavior and the thermochemical processes involved in gasification. The main results include the mapping of fluidization regimes and the determination of the regime at the Mauá SP Pilot Plant using only operational data, in addition to the identification of chemical reaction zones. From the point of view of CFD application, the Eulerian-Eulerian approach was effective for studying fluidization on a large scale, offering precision with reduced computational cost, and can be applied to larger reactors without excessively increasing the complexity of the computational mesh. The research advanced the theoretical understanding of gasification and demonstrated the practical applicability of computational models to improve sustainable industrial technologies.